Antibacterial screening of different part of drumstic tree (Moringa oleifera Lam) - Md. Sarwar, Jahan; Zarizal, Suhaili; Abdulaziz Rabiu, Abdulkadir (2015)
Antimicrobial resistance remains global public health problems. Several pathogenic diseases were found to resist a number of drugs e.g. S. serotypes, S. pneumonia, Enterococcus spp, S. typhimurium, and S. pyogenes among others. However, many other strains of bacterial pathogens were found to develop resistivity against more than one antibiotics, hence this phenomenon is refer to as multidrug resistance. Thus approaches to recover the present condition is needed. This study was aimed to assess antibacterial effect of different part of Moringa oleifera Lam. The results showed that bark and combination of stem with it bark extracts had inhibitory effect against all gram positive bacteria studied. And the most susceptible bacteria was found to be S. aureus (ATTC 33591) while the most resistant one was P. aerogenosa(ATTC 12453). Henceit proves the claimed that many part of Moringa oleifera contains phytochemicals compounds capable of acting as either bacteriostatic or bactericidal activity.